2003
DOI: 10.1007/s00436-003-0947-x
|View full text |Cite
|
Sign up to set email alerts
|

Study of specific IgG subclass antibodies for diagnosis of Gnathostoma spinigerum

Abstract: Gnathostoma spinigerum infection is endemic in Thailand and many Asian countries. Current diagnosis is the skin test and enzyme-linked immunosorbent assay (ELISA) for IgG antibody against the G. spinigerum third-stage larvae (L3), but cross-reactivity is common. We evaluated the sensitivity and specificity of anti-G. spinigerum L3 IgG subclass antibodies for diagnosis of 43 patients with gnathostomiasis. The majority of patients with gnathostomiasis (91%) had eosinophilia. While the anti-G. spinigerum L3 IgG1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 32 publications
3
23
0
1
Order By: Relevance
“…has been useful in the development of a diagnostic tool, as reported for G. spinigerum. 21,22,29 However, in the Pacific region of Mexico, species of Gnathostoma other than G. spinigerum and G. doloresi are responsible for the disease, specifically G. binucleatum. 25 Thus, antigens and immune responses observed in patients infected with other species of Gnathostoma could be different for those observed with patients infected with G. binucleatum.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…has been useful in the development of a diagnostic tool, as reported for G. spinigerum. 21,22,29 However, in the Pacific region of Mexico, species of Gnathostoma other than G. spinigerum and G. doloresi are responsible for the disease, specifically G. binucleatum. 25 Thus, antigens and immune responses observed in patients infected with other species of Gnathostoma could be different for those observed with patients infected with G. binucleatum.…”
Section: Discussionmentioning
confidence: 99%
“…21 However, it has also been reported that total IgG against G. spinigerum shows cross-reactivity with other parasites. 22 We investigated whether antigens of G. binucleatum recognized by total IgG showed any differences in recognition when each IgG subclass was tested by Western blotting. As shown in Table 1 patients with gnathostomiasis caused by G. binucleatum showed IgG1, IgG2, or IgG3 responses against antigens of this parasite.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…comm). Some laboratories use an ELISA for immunoglobulin G subclasses as a screening test (12). In our fi rst patient, the larva was identifi ed based on its morphologic features, including the number and size of cephalic hooks and the character and extent of spines on its body (Figure 2) (2,13).…”
Section: Discussionmentioning
confidence: 99%
“…Posteriormente, se desarrolló una prueba ELISA para la detección de anticuerpos IgG en el tercer estadio de la larva, cuya sensibilidad, según los reportes, no es muy alta (59 a 87 %), en tanto que la especificidad fluctúa entre 79 y 96 %. Tiempo después, Nuchprayon, et al, demostraron que el uso de las subclases de IgG en lugar de la IgG total, mejoraba la sensibilidad y la especificidad de la prueba (27).…”
Section: Caso Clínicounclassified